1999
DOI: 10.1016/s0006-3495(99)77440-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Diffusion Coefficient in Frog Olfactory Cilia

Abstract: Cyclic AMP (cAMP) is one of the intracellular messengers that mediate odorant signal transduction in vertebrate olfactory cilia. Therefore, the diffusion coefficient of cAMP in olfactory cilia is an important factor in the transduction of the odorous signal. We have employed the excised cilium preparation from the grass frog (Rana pipiens) to measure the cAMP diffusion coefficient. In this preparation an olfactory cilium is drawn into a patch pipette and a gigaseal is formed at the base of the cilium. Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 42 publications
6
77
2
Order By: Relevance
“…The latter, voltage profile within the cilium, will be calculated and examined below. It has been reported for detached ciliary preparation that the cytoplasmic cAMP diffusion coefficient is 2.7 ϫ 10 Ϫ6 cm 2 /s (Chen et al, 1999). Therefore, with x (average movement) ϭ (2Dt) 1/2 , the total cilia (20 m length) could be filled with the cAMP within 1 s. However, experimental data observed here are inconsistent with such simple idea.…”
Section: Summation Of Large Local Responsescontrasting
confidence: 59%
“…The latter, voltage profile within the cilium, will be calculated and examined below. It has been reported for detached ciliary preparation that the cytoplasmic cAMP diffusion coefficient is 2.7 ϫ 10 Ϫ6 cm 2 /s (Chen et al, 1999). Therefore, with x (average movement) ϭ (2Dt) 1/2 , the total cilia (20 m length) could be filled with the cAMP within 1 s. However, experimental data observed here are inconsistent with such simple idea.…”
Section: Summation Of Large Local Responsescontrasting
confidence: 59%
“…Although the diffusion of cAMP has long been considered to be fast within cells, recent studies have suggested that enzymes involved in cAMP synthesis and degradation generate boundaries for cAMP diffusion [7][8][9]16,17]. Studies in HEK293 cells where rat olfactory CNG channels, which have been modified to be sensitive to cAMP, were overexpressed have illustrated that distinct cAMP signals coexist within these cells [10].…”
Section: Dynamic Camp Gradientsmentioning
confidence: 99%
“…cAMP diffusion from the membrane toward the cytosol can be one factor, but studies in frog olfactory cilia (Chen et al, 1999), cultured hippocampal neurons (Nikolaev et al, 2004), and cardiocytes (Saucerman et al, 2006) have shown a diffusion speed of tens of micrometers per second, which cannot account for the kinetic differences observed between the membrane compartment and the cytosol. Endogenous buffers may also contribute to slowing down the propagation of the signal, as suggested by modeling studies (Rich and Karpen, 2002;Saucerman et al, 2006).…”
Section: Time Coursementioning
confidence: 99%